ANALISIS KEMAMPUAN KOGNITIF PESERTA DIDIK DALAM MENYELESAIKAN SOAL PADA MATERI KALOR DAN PERPINDAHANNYA - Perawani Perawani; Tomo Djudin; Hamdani Hamdani (Universitas Tanjungpura, 2019)
AbstractThis researc aimed to find student cognitive ability in answering questions about the material of heat and its transfer in class VII SMP Santa Monika. The method used in this research is descriptive survey method which aimed to find information by analyzing the ability of students in answering questions in the from of test of factual, conceptual and procedural knowledge. The instrument of data collections uses 15 essay tests, consisting of 5 factualn knowledge questions, 5 conceptual knowledge questions, and 5 procedural knowledge questions. The analysis of gender-based cognitive ability data in each aspect of the knowledge, factual, conceptual, and procedural dimensions for male students is equal to, 74%, 26%, and 7%, while the results for female students are 72%, 26%, and 12%, with the results of the average percentage of student cognitive ability being 36% for male and 38% for female students. The results of the independent sample t-test showed that there was no difference between the cognitive ability of male and female students in answering the questions which was evidenced by the tcalc value < ttable ( t0 = -1,190 < ttable = 1,675 ). This research is expected to be used as a reference for future students to improve cognitive abilities in the knowledge dimension. Keywords: Cognitive ability, Conceptual knowledge, Factual knowledge, Heat and transfer, Knowledge dimension, Procedural knowledge